FMRI of spinal and supra‐spinal correlates of temporal pain summation in fibromyalgia patients. Issue 4 (9th January 2016) - Bosma, Rachael L.; Mojarad, Elham Ameli; Leung, Lawrence; Pukall, Caroline; Staud, Roland; Stroman, Patrick W.
Abstract: Fibromyalgia syndrome (FM) is a debilitating chronic pain condition, which afflicts primarily females. Although the etiology of this illness is not completely understood, FM pain is thought to rely on enhanced pain sensitivity maintained by central mechanisms. One of these mechanisms is central pain amplification, which is characterized by altered temporal summation of second pain (TSSP). Here we use a TSSP paradigm and functional MRI (fMRI) of the spinal cord, brainstem, and brain to noninvasively examine the central nervous system contributions to TSSP in FM patients and normal controls (NC). Functional MRI of pain‐free female adults ( N  = 15) and FM patients ( N  = 14) was conducted while brief, repetitive heat pain stimuli (0.33 Hz) were applied to the thenar eminence of the hand (C6 dermatome). The stimulus intensity was adjusted to each participant's heat pain sensitivity to achieve moderate pain. Data were analyzed by means of a General Linear Model and region‐of‐interest analyses. All participants demonstrated significant pain summation in the TSSP condition. FM subjects, however, required significantly lower stimulus intensities than NC to achieve similar TSSP. fMRI analyses of perceptually equal TSSP identified similar brain activity in NC and FM subjects; however, multiple areas in the brainstem (rostral ventromedial medulla and periaqueductal grey region) and spinal cord (dorsal horn) exhibited greater activity in NC subjects. Finally, increased after‐sensations and enhanced dorsal horn activity was demonstrated in FM patients. In conclusion, the spinal and brainstem BOLD responses to TSSP are different between NC and FM patients, which may indicate alterations to descending pain control mechanisms suggesting contributions of these mechanisms to central sensitization and pain of FM patients. Hum Brain Mapp 37:1349‐1360, 2016 . © 2016 Wiley Periodicals, Inc.